دائرية الإخفاق في أنشودة المطر لبدر شاكر السياب - سلام، حفيظة قاسم (جامعة الملك خالد, 2015)
تحاول هذه الدراسة أن تقرأ أنشودة المطر لبدر شاكر السياب قراءة تأويلية تطبق خلالها إجراءات هذه القراءة معتمدة على منهج الهيرمنيوطيقا المتطور لدى هيرشو جادامير، كما تأخذ ما يتفق من آراء ويلهلم ديلثاي الذي أفاد من الحلقة الهيرمنيوطيقية. وتحدد الدراسة هدفها في الوقوف على قصد المؤلف كما عبر عنه النص، وإضاءة معنى احتمالي نسبي ينتهي به إلى تأويل مشروع. وتنهض على ثلاثة محاور يبرز الأول منها انعكاس هذا المعنى الاحتمالي على هندسة النص، ويوضح الثاني كيف أسهمت الصورة الفنية في تشكيل هذا المعنى، ويقف الثالث على الدور البنائي والدلالي الذي يختص به الإيقاع داخل النص.
This study sought to provide an interpretive analysis of Bader Shaker As-Sayyab's Rain Ode, the perusal of which was deeply grounded in the procedures of Hans-Georg Gadamer's hermeneutics and the hermeneutic philosophy of Wilhelm Dilthey who developed hermeneutics a bit further after Gadamer's. The aim of the study was to delve deeply into the purpose of the poet as tacitly expressed in the text of the ode and illuminate relative probabilities in the interpretation of the ode's text. The study is set in three sections, the first of which reflects probability exegesis as is palpable in the architecture of the text and its engineering. The second section explicates how figures of speech contributed to creating this interpretation. Finally, the third section highlights the role of lexical structure and semantics in creating rhythm in the ode's text.
Keywords: الأدب العربي -- الأدباء العرب -- النقد الأدبي -- الدراسات الأدبية -- أنشودة المطر -- السياب ، بدر شاكر -- مستخلصات الأبحاث